MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATERI GENETIKA DENGAN MEDIA KANCING MENGGUNAKAN MODEL NUMBERED HEAD TOGETHER (NHT) - Astri Sri Muriani (Universitas Lambung Mangkurat, 2017)
Abstract. This study aims to determine the increase student activity on Genetic material at class IX A SMP Negeri 13 Banjarmasin. This research is a classroom action research conducted in 2 cycles. Each cycle consists of planning, implementation, observation/evaluation and analysis/reflection. The subjects of the study were the students of class IX A of SMP Negeri 13 Banjarmasin, amounting to 32 students. Techniques of collecting data using test and observation. The results showed that the achievement of science learning especially genetic material using NHT model increased from 63.8 in cycle I to 90.3 in cycle II. Achievement of science learning especially genetic material using NHT model increased its completeness by classical from 44% in cycle I to 96,9% in cycle II. Student activity increased from 43 (active) in cycle I to 84 (very active) in cycle II. Activity of teachers from 33 (active) in cycle I to 40 (active) in cycle II. Student responses were positive or agreed 89% with use of the NHT model on Genetic material. Students respond positively to learning using NHT method and buttons media.Keywords: student activities, NHT model, genetics material